A NEW SPLITTING METHOD FOR MONOTONE INCLUSIONS - Van Dung, Nguyen; Thi Kim Hoa, Hoang; Thi Hue , Nguyen; Thi Thao, Ha (HNUE Journal of Science: Journal of Natural Sciences, 2024)
In this paper, we propose a splitting method for finding a zero point of the sum of two operators in Hilbert spaces. Our method is a modification of the forward-backward algorithm by using the inertial effect. Under the imposed condition for parameters, weak convergence of the iterative sequence is established. We also give some numerical experiments to demonstrate the efficiency of the proposed algorithm.